Pengaruh Struktur Aktiva dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Pertambangan yang Terdaftar di BEI - Fitria, Vivi Lailatul; Jamal, Sri Wahyuni; Rahmah, Asmadhini Handayani (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of asset structure and managerial ownership on company value in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The method used in this study is a quantitative approach with multiple linear regression analysis techniques. Sample selection was carried out using the purposive sampling method, with a sample size of 15 companies. Company value is measured using the price to book value (PBV) ratio, asset structure is determined through the proportion of fixed assets to total assets. Managerial ownership is measured based on the percentage of share ownership by management. The results of the study indicate that asset structure does not have a significant effect on company value. On the contrary, managerial ownership is proven to have a significant effect. This finding indicates that management involvement in share ownership can strengthen the relationship between the interests of managers and shareholders, thus motivating decision making that has a positive impact on company value. This study contributes to enriching the literature on factors that influence company value and becomes a consideration for management and investors in developing strategies to increase company value in the mining sector.